Comparative Analysis of the Altman Z-Score and Springate Models in Predicting Bankruptcy of Pharmaceutical Companies in Indonesia - Yenita Indahyana Rahma; Hellena Benedicta; Gaby Novita (Research Collaboration Community (RCC), 2025)
The pharmaceutical industry is an important sector that not only focuses on making profit but also has a social responsibility to support public health. During the COVID-19 pandemic, this industry became much more active, especially in importing raw materials and producing medicines and health supplements. However, this growth also came with a large increase in debt, which raised the risk of financial problems. To deal with this, several bankruptcy prediction models have been developed, such as the Altman Z-Score and Springate models. These models are often used as early warning systems in many industries. Even so, research on bankruptcy prediction in Indonesian pharmaceutical companies is still limited. Therefore, this study aims to compare the two models in predicting bankruptcy in Indonesian pharmaceutical firms. The results show that the Altman Z-Score model is more suitable for long-term prediction, while the Springate model works better for short-term prediction.